PENGARUH GAYA MENGAJAR RESIPROKAL TERHADAP HASIL BELAJAR BERMAIN FUTSAL - Asep Sahrul Gunawan, - (2018)
This study aims to determine the effect of reciprocal teaching style on the results of learning to play futsal. The research method used is a quasi-experimental research method. The population used as the object of research is students of SMA Negeri 1 Jampangkulon who take futsal extracurricular activities. Samples in the study amounted to 20 students who were taken by incidental sampling. The instrument used is GPAI (Game Performance Assessment Instrument). The results of processing and analysis of hypothesis testing data with a significance of 0.05 where in the reciprocal teaching style group the value of Tcount was -6.026 <T table 1.725. It can be concluded that reciprocal teaching style affects the results of learning to play futsal ;---Penelitian ini bertujuan untuk mengetahui pengaruh gaya mengajar resiprokal terhadap hasil belajar bermain futsal. Metode penelitian yang digunakan adalah metode penelitian quasi eksperimen. Populasi yang dijadikan objek penelitian adalah siswa SMA Negeri 1 Jampangkulon yang mengikuti ekstrakurikuler futsal. Sampel pada penelitian berjumlah 20 siswa yang diambil dengan cara sampling insidental. Instrumen yang digunakan adalah GPAI (Game Performance Assessment Instrument). Hasil pengolahan dan analisis data uji hipotesis dengansignifikansi 0,05 dimana pada kelompokgayamengajarresiprokalnilaiThitungsebesar -6,026 <Ttabel 1,725. Dapatdisimpulkanbahwagaya mengajar resiprokalberpengaruhterhadaphasilbelajar bermain futsal.